NORMATIVE MODERATORS OF IMPULSE BUYING BEHAVIOR - Danes Jaya Negara; Basu Swastha Dharmmesta (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
Prior research has presented the moderating role of normative evaluations in the relationship between the impulsive buying trait and consumers’ buying behaviors. In this article the authors show that consumer tendency to buy something spontaneous, unreflectively and immediately can be perceived as a factor which describes buying impulsiveness. This article also shows conceptual and empirical evidence that there is some support for the moderating role of normative evaluations in the relationship between buying impulsiveness and impulse buying behaviors. Significance occurs when consumers believe that act on impulse is suitable. The result suggests that consumers’ normative evaluation can moderate the link between the trait and behavioral aspects of impulse buying.